(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
Pumpkin fingers were treated with a calcium solution with different concentrations as well as different durations. The calcium concentrations, the percentages contents of moisture and ash were were estimated in the samples before and after the treatment with a sugar solution, Also, the hardness of the samples was studied and linked to the concentration of calcium in the samples to determine the effect of the soaking process on absorption of calcium from pumpkin samples. Finally, pumpkin fingers sweet was evaluated in terms of colour, taste, shape and texture. It was found that the treatment with the calcium solution had a positive effect on the hardness of the Pumpkin fingers texture among the range of used concentrations (2.5% - 5%) for different durations (4 - 16) hr, however it had a negative effect on the colour and taste when treatment duration was increased for more than 12 hr. The sugar solution (pre-treatment 25%, main treatment 50%) also had a role in reducing the activity water and improving the final taste of the Pumpkin fingers sweet. تمَّت مُعاملة أصابع القرع بمحلولٍ كلسي بتراكيز مختلفةٍ وأزمنةٍ مختلفةٍ، ثمَ تمَّ تقدير تراكيز الكالسيوم والرطوبة والرماد في العينات قَبلَ وبعد المعاملة بالمحلول السكري، كما تمَّ تقدير درجة صلابة أصابع حلوى القرع وربطها بتركيز الكالسيوم في العينات، للوقوف على تأثير عملية النقع على دخول الكالسيوم إلى عينات القرع، كما تمَّ تقييم أصابع حلوى القرع حسياً من حيث اللون والطعم والشكل الخارجي والقوام. وُجِدَ التأثير الإيجابي للمعاملة بالمحلول الكلسي على قوام (صلابة) أصابع حلوى القرع ضمن حدود التراكيز المستخدمة (2.5%- 5%) طبقاً للفترات الزمنية التي تراوحت بين (4- 16) ساعة، في حين كان تأثيره سلبياً على اللون والطعم عند زيادة مدّة معاملة العينات بهذا المحلول عن 12 ساعة، كما كان للمحلول السكري بتركيز أوَّلي 25% وآخر 50% دوراً في تخفيض النشاط المائي وتحسين الطعم النهائي لأصابع القرع.